2022
DOI: 10.1186/s13014-022-02052-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of therapy resistance and transcriptomic profiling data in glioblastoma cells identifies sensitization vulnerabilities for combined modality radiochemotherapy

Abstract: Background Inherent resistance to radio/chemotherapy is one of the major reasons for early recurrence, treatment failure, and dismal prognosis of glioblastoma. Thus, the identification of resistance driving regulators as prognostic and/or predictive markers as well as potential vulnerabilities for combined modality treatment approaches is of pivotal importance. Methods We performed an integrative analysis of treatment resistance and DNA damage resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that LN18 cells are more resistant to TMZ than U87 cells . TMZ is a chemotherapy commonly prescribed with radiotherapy as the first line of defense against GBM since it is one of a few cancer drugs that can penetrate the blood–brain barrier .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that LN18 cells are more resistant to TMZ than U87 cells . TMZ is a chemotherapy commonly prescribed with radiotherapy as the first line of defense against GBM since it is one of a few cancer drugs that can penetrate the blood–brain barrier .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LN18 cells are more resistant to TMZ than U87 cells. 36 TMZ is a chemotherapy commonly prescribed with radiotherapy as the first line of defense against GBM since it is one of a few cancer drugs that can penetrate the blood–brain barrier. 37 TMZ has toxic side effects and is not a transcription-independent method of targeting cancer cells, so GBM cells can become resistant to the therapy, resulting in tumor reoccurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the mechanism of cell death is not primarily due to lipid peroxidation. This finding is of particular importance because U251 cells are considerably more resistant to ionizing radiation than other glioblastoma cell lines, and POM-based nanoparticle platforms may provide a novel therapeutic outlet to overcome resistance [ 26 ]. Thus, both Mo- and W-POMs may have therapeutic potential in glioblastoma cells by serving as a reserve of redox-active metals to induce cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoradiotherapy resistance is an important element to early recurrence, treatment failure and dismal prognosis of glioblastoma 277 . With growing amounts of evidence that chemoradiotherapy may induce the more normal cells to glioma leading to recurrence and progression 278,279 .…”
Section: Ppis Sensitize Chemoradiotherapy Promoting Apoptosismentioning
confidence: 99%
“…Chemoradiotherapy resistance is an important element to early recurrence, treatment failure and dismal prognosis of glioblastoma. 277 With growing amounts of evidence that chemoradiotherapy may induce the more normal cells to glioma leading to recurrence and progression. 278 , 279 Even if the concentration of drugs entering plasma and cerebrospinal fluid is enough to inhibit the progression of the tumour, the drug resistance and progression of glioma also happen from time to time.…”
Section: Ppis Sensitize Chemoradiotherapy Promoting Apoptosismentioning
confidence: 99%